Large community-acquired Legionnaires’ disease outbreak caused by Legionella pneumophila serogroup 1, Italy, July to August 2018 - Faccini, Marino; Russo, Antonio Giampiero; Bonini, Maira; Tunesi, Sara; Murtas, Rossella; Sandrini, Monica; Senatore, Sabrina; Lamberti, Anna; Ciconali, Giorgio; Cammarata, Serafina; Barrese, Eros; Ceriotti, Valentina; et al. (Euro surveillance : bulletin européen sur les maladies transmissibles, 2020)
In July 2018, a large outbreak of Legionnaires’ disease (LD) caused by Legionella pneumophila serogroup 1 (Lp1) occurred in Bresso, Italy. Fifty-two cases were diagnosed, including five deaths. We performed an epidemiological investigation and prepared a map of the places cases visited during the incubation period. All sites identified as potential sources were investigated and sampled. Association between heavy rainfall and LD cases was evaluated in a case-crossover study. We also performed a case–control study and an aerosol dispersion investigation model. Lp1 was isolated from 22 of 598 analysed water samples; four clinical isolates were typed using monoclonal antibodies and sequence-based typing. Four Lp1 human strains were ST23, of which two were Philadelphia and two were France-Allentown subgroup. Lp1 ST23 France-Allentown was isolated only from a public fountain. In the case-crossover study, extreme precipitation 5–6 days before symptom onset was associated with increased LD risk. The aerosol dispersion model showed that the fountain matched the case distribution best. The case–control study demonstrated a significant eightfold increase in risk for cases residing near the public fountain. The three studies and the matching of clinical and environmental Lp1 strains identified the fountain as the source responsible for the epidemic.